ВИЗНАЧЕННЯ ВПЛИВУ СКЛАДУ ПАЛИВА І РІВНЯ НАВАНТАЖЕННЯ НА ЕНЕРГОЕФЕКТИВНІСТЬ АВТОНОМНИХ ДЖЕРЕЛ ЖИВЛЕННЯ З ІСКРОВИМ ЗАПАЛЮВАННЯМ - Зайченко, С.В.; Кулиш, Р.Д. (Інститут електродинаміки Національної академії наук України, 2023)
This work presents a new approach to determining energy indicators, such as specific fuel consumption and the energy efficiency ratio of a power generating plant. The essence of the new method is to determine the instantaneous power of the installation followed by data processing through integration. The use of this method made it possible to establish the dependence of specific energy indicators on the load level of the generating plant. The established distribution allows you to determine the optimal parameters of the experimental installation and consumption at different load levels. The highest specific fuel energy consumption is observed (1189-1297 g/(kW⋅h) and 962-1147 g/(kW⋅h)) at the lowest and heaviest load with different types of fuel. Experimental data confirmed that fuel without ethanol impurities allows generating a larger amount of electrical energy, which is advisable to use when greater needs arise.. Bibl 8. Fig. 2